The use of teaching methods by the teachers who work at high schools and the reasons of their preference (Ankara province sample) - Gökhan Acar; Haluk Koc; Mustafa Koc (Türk Spor ve Egzersiz Dergisi)
In this study, the aim is to determine teaching methods that physical education teachers at elementary schools in Ankara use and to define why they prefer those methods. The research group contains 88 physical education teachers. 19 of them are female and 69 of them are male. The questionnaire of the study conducted to a sample group of 30 individuals for its reliability and validity. After the analysis conducted, the factor number was observed to be 2 and the total variance of the test was calculated as 21.083. Reliability study was conducted using Cronbach Alfa (a) Internal Consistency Method and “0.88”figure was found. Findings, showed that participants were experienced teachers at the age of “42 and above “, also their teaching experience was “21 years and above.”  It also showed that more than half of them attended “in-service training” about teaching methods, that they often use “demonstration”, “practice and “narration” methods and that they rarely use “assignment method”. They think students like demonstration method most. They support the idea that the most important reason while deciding on the teaching method is its convenience to the “opportunities of the school”, “course duration” and “the properties of physical education lesson”. As a result, property and size of the learning group, teacher's tendency to the method, duration, physical opportunities, financial sources and prospective behaviours should be taken into account while choosing the teacing method.Also there is a need of organizing in-service training courses in the field of teaching techniques to the teachers and of a cooperation between universities and Ministry of National Education in order to lead teachers to the use of teching methods and techniques.